Posttraumatic stress disorder : from neurobiology to treatment - Bremner, J. Douglas, 1961- (Hoboken, New Jersey : Wiley/Blackwell, 2016)
Posttraumatic Stress Disorder: From Neurobiology to Treatment presents a comprehensive look at this key nEuropsychiatric disorder. The text examines the neurobiological basis of post-traumatic stress and how our understanding of the basic elements of the disease have informed and been translated into new and existing treatment options. The book begins with a section on animal models in posttraumatic stress disorder research, which has served as the basis of much of our neurobiological information. Chapters then delve into applications of the clinical neuroscience of posttraumatic stress disorder. The final part of the books explores treatments and how our basic and clinical research is now being converted into treatment. Taking a unique basic science to translational intervention approach, Posttraumatic Stress Disorder: From Neurobiology to Treatment is an invaluable resource for researchers, students and clinicians dealing with this complex disorder.
Posttraumatic stress disorder : from neurobiology to clinical presentation / Arieh Shalev, J. Douglas Bremner -- The epidemiology of PTSD in children and adolescents : a critical review / Leah A. McGuire -- Early life stress and development : preclinical science / Dora B. Guzman, Brittany R. Howell, Mar Sanchez -- Amygdala contributions to fear and safety conditioning : insights into PTSD from an animal model across development / Christopher Cain, Regina Sullivan -- Preclinical evidence for benzodiazepine receptor involvement in the pathophysiology of PTSD, comorbid substance abuse and alcoholism / Robert Drugan, Nathaniel P. Stafford, Timothy A. Warner -- Psychosocial predator stress model for PTSD based on clinically relevant risk factors for trauma-induced psychopathology / Phillip R. Zoladz, David Diamond -- Coping with stress in wild birds : the evolutionary foundations of stress responses / Molly J. Dickens, Michael Romero -- Stress, fear, and memory in healthy human subjects / Christian Merz, Bernet Elzinga, Lars Schwabe -- Neurotransmitter, neurohormonal, neuropeptidal and immune function in stress and PTSD / J. Douglas Bremner, Brad Pearce -- Genomics of posttraumatic stress disorder / Anthony S. Zannas, Elisabeth Binder, Divya Mehta -- Cortisol and the hypothalamic-pituitary-adrenal (HPA) axis in PTSD / Amy Lehrner, Nicolaos Daskalakis, Rachel Yehuda -- Neuroimaging of posttraumatic stress disorder / Carolina Campanella, J. Douglas Bremner -- Posttraumatic stress disorder and mild traumatic brain injury / J. Douglas Bremner -- Stress-related psychopathology and pain / Sarah C. Reitz, Karl-Juergen Bar, Christian Schmahl -- Stress and health / Vaccarino Vaccarino. Emeran Mayer, J. Douglas Bremner -- Pharmacotherapy for PTSD : effects on PTSD symptoms and the brain / Lori Davis, Mark Hamner, J. Douglas Bremner -- Effects of psychotherapy for psychological trauma on PTSD symptoms and the brain / J Douglas Bremner, Carolina Campanella.
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher.
Keywords: Post-traumatic stress disorder; Stress (Psychology); HEALTH & FITNESS / Diseases / General; MEDICAL / Clinical Medicine; MEDICAL / Diseases; MEDICAL / Evidence-Based Medicine; MEDICAL / Internal Medicine; Post-traumatic stress disorder; Stress (Psychology); Stress Disorders, Post-Traumatic.; Stress, Psychological; Electronic books